2012
DOI: 10.1002/etc.1798
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis on parameters and processes affecting vapor intrusion risk

Abstract: A one‐dimensional numerical model was developed and used to identify the key processes controlling vapor intrusion risks by means of a sensitivity analysis. The model simulates the fate of a dissolved volatile organic compound present below the ventilated crawl space of a house. In contrast to the vast majority of previous studies, this model accounts for vertical variation of soil water saturation and includes aerobic biodegradation. The attenuation factor (ratio between concentration in the crawl space and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Local equilibrium of PCE in all phases—soil gas, soil water and soil—was assumed. While some studies (Cho et al , 1993) showed the effect of considering mass transfer rate at interfaces, assumption of local equilibrium are found to be common (Grifoll and Cohen, 1996) and sufficient (Picone et al , 2012), and this is shown in the constitutive Equations (11) and (12). Contaminant diffusion in soil gas and soil water was expressed by Millington-Quirk (Millington and Quirk, 1961) Equation (14), while other methods, such as (Kristensen et al , 2010) give similar modeling results (Shen et al , 2012; Shen et al , 2011).…”
Section: Methodology and Validation Of The Infiltration Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Local equilibrium of PCE in all phases—soil gas, soil water and soil—was assumed. While some studies (Cho et al , 1993) showed the effect of considering mass transfer rate at interfaces, assumption of local equilibrium are found to be common (Grifoll and Cohen, 1996) and sufficient (Picone et al , 2012), and this is shown in the constitutive Equations (11) and (12). Contaminant diffusion in soil gas and soil water was expressed by Millington-Quirk (Millington and Quirk, 1961) Equation (14), while other methods, such as (Kristensen et al , 2010) give similar modeling results (Shen et al , 2012; Shen et al , 2011).…”
Section: Methodology and Validation Of The Infiltration Modelmentioning
confidence: 99%
“…Tillman and Weaver (2007) studied the influence of temporal soil moisture changes and suggested that soil moisture content measurements taken somewhere other than beneath a building of interest could not be reliably used to calculate the indoor vapor concentration effects. While infiltration was not addressed in most other field and modeling studies, other transient factors, such as groundwater level fluctuations (Picone et al , 2012), and groundwater concentration fluctuation (Folkes et al , 2010) were discussed. Short term fluctuation might have little or no effect, but the definition of “short term” or “long term” might be site specific and will need more research to define (Folkes et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the higher attenuation, i.e. the lower lateral screening distance, obtained in the case of groundwater contamination is due to the presence of the capillary fringe that, as known, strongly limits the vapor migration due to the low effective air-phase porosity (Shen et al, 2012;Picone et al, 2012). The lateral exclusion criteria described above can be drastically reduced depending on the source concentration.…”
Section: Estimation Of Lateral Screening Distancementioning
confidence: 96%
“…Eklund and Simon, 2007; and USEPA, 2010). To explain observed variations, several existing studies have attempted to investigate uncertainties in input parameters to vapor intrusion models, as well as, the sensitivity of these models to changes in the inputs (Johnson, 2005; Hers et al, 2001; Hers et al, 2003; Tillman and Weaver, 2006; Tillman and Weaver, 2007; Yu et al, 2009; Johnston and Gibson, 2011; Picone et al, 2012). The large variations in input parameters for vapor intrusion models, as well as discrepancies between the vapor intrusion model predictions and field measurements, highlights the need for additional research to investigate the uncertainty and sensitivity of vapor intrusion models.…”
Section: Introductionmentioning
confidence: 99%
“…Picone et al (2012) developed a one-dimensional numerical model in order to identify the critical parameters that generate large variation in model output. Three important parameters including relative distance of the sources to the nearest gas-filled pores in unsaturated zones, biodegradation and water table oscillations in aquifer were identified as major contributing factors in attenuation factor.…”
Section: Introductionmentioning
confidence: 99%